2011
DOI: 10.1158/0008-5472.can-10-3145
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Causes Cardiac Atrophy and Autophagy in a Sexually Dimorphic Manner

Abstract: Approximately one-third of cancer deaths are caused by cachexia, a severe form of skeletal muscle and adipose tissue wasting that affects men more than women. The heart also undergoes atrophy in cancer patients, but the mechanisms and the basis for apparent sex differences are unclear. In a mouse colon-adenocarcinoma model, cancer causes a loss of cardiac mass due to a decrease in cardiac myocyte size that is associated with reduced levels of all sarcomeric proteins. Unlike skeletal muscle cachexia, atrophic h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
189
6
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(224 citation statements)
references
References 50 publications
22
189
6
7
Order By: Relevance
“…Cardiac dysfunction is independently associated with substantial morbidity and mortality in cachexia, and its mechanistic underpinnings are therefore an important topic of investigation. Cardiac muscle catabolism in cachexia has previously been linked to induction of autophagy and variably to expression of atrophy‐associated ubiquitin ligases 46, 47. Our data establish that the KPC model is similar to other cachexia models by producing skeletal muscle catabolism by E3 ubiquitin ligase activation and cardiac muscle catabolism via autophagy, but that both pathways are active in both tissue subsets.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Cardiac dysfunction is independently associated with substantial morbidity and mortality in cachexia, and its mechanistic underpinnings are therefore an important topic of investigation. Cardiac muscle catabolism in cachexia has previously been linked to induction of autophagy and variably to expression of atrophy‐associated ubiquitin ligases 46, 47. Our data establish that the KPC model is similar to other cachexia models by producing skeletal muscle catabolism by E3 ubiquitin ligase activation and cardiac muscle catabolism via autophagy, but that both pathways are active in both tissue subsets.…”
Section: Discussionsupporting
confidence: 67%
“…Importantly, the rate of muscle wasting and weight loss correspond to survival in cancer patients,70, 71 and males experience an increased degree of catabolism and an increased mortality risk in many different subsets of cancer 72, 73, 74. In the C26 model of cancer cachexia, male mice experience greater body weight loss, loss of skeletal and cardiac muscle, and mortality than tumour‐bearing females because of the protective effects of oestrogen receptor signalling 46. Our model demonstrates for the first time that LMA changes are sexually dimorphic and in females are the first behavioural signal of cachexia onset.…”
Section: Discussionmentioning
confidence: 99%
“…30 Cancer cachexia animal models are showing significant wasting of the myocardium. [31][32][33] In one study it was shown that the heart muscle weight is decreased by 20% on average. 34 In another cancer cachexia study, cardiac wasting was associated with left-ventricular (LV)-dysfunction.…”
Section: Current Developments On Muscle Mass Lossmentioning
confidence: 99%
“…Interestingly, estrogen is also able to influence autophagy. 37,38) Whether GRb1 could modulate autophagy through ERrelated pathways also requires future investigation.…”
Section: )mentioning
confidence: 99%